Shia Belief and National Security in Malaysia: The Securitisation - Othman, Zarina; Idris, Nor Azizan; Daud, Abdul Halim (Afkar: Jurnal Akidah dan Pemikiran Islam, 2022)
The world’s politics was stunned by the actualisation of the Iranian Revolution in 1979. Ayatollah Ruhollah Khomeini overthrew the Pahlavi Dynasty under the rule of the Shah of Iran. The Revolution portrayed a positive impression of Shia, the official state religion of Iran, and gained support from many Islamic countries including Malaysia. However, after more than three decades, some countries have proposed that Shia teachings may contradict the beliefs of Ahl al-Sunnah wa al-Jama‘ah (Sunni teachings). Sunni-Shia struggle, as occurring in Syria and Iraq, portrayed the clash between the two sects of Islamic teachings. Malaysia, a country that practices Sunni Islamic teachings has decided to ban Shia through a decree issued by the National Fatwa Committee in 1996. The purpose of this study was to analyse how Shia teachings are linked to national security. This study was based on the securitisation approach as a tool of analysis through the speech acts and views of the securitisation actors. The study also gathered primary data from interviews and field observations conducted in Iran and Malaysia. Meanwhile, secondary data were collected from reliable printed materials such as academic research books, local and international reviewed journals, newspaper clippings, government reports and authoritative webpages. The findings suggest that even though Shia teachings are not declared by the country as a national security threat, it has the potential to raise public safety issues such as creating disharmony among the followers of the Sunni Islamic community, drawing a wedge in the unity of the Muslim community and may also undermine the national sovereignty.